Extended Reality for Healthcare Systems : Recent Advances in Contemporary Research - Alam, Dr. Mansaf; Banday, Shoaib Amin.; Usta, Mohammed Shaukat (London : Elsevier, 2023)
The book includes case studies that break down the ways in which this technology has and can be used, while also taking readers through evidence, best practices and obstacles. Sections emphasize evidence, research-based practices and work. --
Includes bibliographical references.
Online resource; title from title screen (Skillsoft Books).
Keywords: Health Facility Administration; Workflow